THE SURVEY OF THE BARRIERS TO NOT REPORTING MEDICATION ERRORS FROM THE PERSPECTIVE OF NURSING STUDENTS - Pournamdar, Zahra; Zare, Sadegh; Shameli, Alireza; Jafari, Hossein (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Reporting the medication errors, on the one hand, causes the preservation and observation of the patient security, and on the other hand, it is regarded as a valuable information treasure in line with the prevention of the medication errors expression in the future. Therefore, the present study has been conducted with the objective of the survey of barriers to medication errors reporting from the perspective of the nursing students. Methods: This study is a descriptive research which has been conducted on 87 nursing students who have been selected based on a random method. To gather the required information, there has been made use of a two-part questionnaire, the first part of which deals with the study of the demographic characteristics and the second part pertains to the factors influencing not reporting the medication errors. In the end, after the necessary information collected the data were analyzed by taking advantage of SPSS 19 and descriptive statistics. Results: The individuals average age in the present study was 21.09Â±2.48, 51 individuals were female. 24 individuals were studied in semester 4, 31 people were passing term 6, and 32 individuals were in term 8. The highest mean score as obtained in managerial aspect. In addition, the highest mean score was related to the items concentration of the managers solely on the person who has made the mistake and disregarding of the other factors involved in mediation errorâ€ and lack of receiving a positive feedback from the nursing supervisors following reporting the medication errorâ€ and the lowest mean score was related to the item not being considerate to some of the medication errors reporting.â€ Conclusion: The results of this study indicated that the highest mean score for not reporting the medication errors went to the managerial dimensions. Therefore, the supervisors and the nursing staff should be cautioned regarding their behavior, regarding the medication errors reporting, and consider the problems and issues systematically. Keywords: Medication error, University students, Zahedan, Nursing.